2020
DOI: 10.18502/ijhoscr.v14i1.2362
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiles of MV4-11 and Kasumi 1 Acute Myeloid Leukemia Cell Lines Modulated by Epigenetic Modifiers Trichostatin A and 5-Azacytidine

Abstract: Background: Acute myeloid leukemia (AML) is the most common form of acute leukemias in adults which is clinically and molecularly heterogeneous. Several risk and genetic factors have been widely investigated to characterize AML. However, the concomitant epigenetic factors in controlling the gene expression lead to AML transformation was not fully understood. This study was aimed to identify epigenetically regulated genes in AML cell lines induced by epigenetic modulating agents, Trichostatin A (TSA) and 5-Azac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 48 publications
3
7
0
Order By: Relevance
“…Therefore, it suggested that JOA induces monocyte/macrophages differentiation of THP-1 cells, and activates the phagosome pathway. The result is in accordance with that phagosome pathway was commonly activated in both MV4-11 and Kasumi-1 AML cell lines treated with differentiation inducers, trichostatin A and 5-azacytidine (33).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, it suggested that JOA induces monocyte/macrophages differentiation of THP-1 cells, and activates the phagosome pathway. The result is in accordance with that phagosome pathway was commonly activated in both MV4-11 and Kasumi-1 AML cell lines treated with differentiation inducers, trichostatin A and 5-azacytidine (33).…”
Section: Discussionsupporting
confidence: 90%
“…Aberrant methylation of TSGs is involved in the pathogenesis of several cancers [7]. The expression of TSGs, such as the JAK/STAT-negative regulator genes, is silenced due to hypermethylation of the CpG islands in promoter regions, leading to the malignant transformation of normal hematopoietic cells and the development of leukemia [7,8]. Different levels of DNA methylation have been implicated in the development and prognosis of AML [8].…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic silencing of tumor suppressor genes (TSGs) by DNA hypermethylation has a critical role in the development of leukaemia, including AML [7,8]. Unlike genetic dysregulation, the epigenetic alterations are reversible, making them attractive targets for anticancer therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that phagosome pathway is the most optimal and common in both Kasumi-1 and MV4-11 AML cell lines induced by differentiation inducers, Trichostatin A and 5-Azacytidine ( Asmaa et al, 2020 ). Moreover, the phagosome pathway is involved in the MHC II and antigen processing and presentation (KEGG map 1 ).…”
Section: Discussionmentioning
confidence: 99%